Teacher’s reports on educational practices for inclusion during the pandemic: the experiences from the Rio de Janeiro’s council educational network (Olhar de Professor, 2021)
The present research has been undertaken with Elementary School teachers of the Rio de Janeiro´s council educational network, specifically in classes with students with disabilities. Based on the everyday classroom routine, we seek to “understand the educational practices of teachers for the inclusion of students with disabilities during the Covid-19 pandemic”. The research followed the assumptions of the epistemology of practice and the chosen research method was the “research the experience”. The WhatsApp mobile application has been used to talk to the teachers and to ask them to share their experiences through an online form, which was organized into open topics on teaching activities for the inclusion of students during the pandemic. As the results of this research we highlight the following potentialities - multiple teaching inventiveness for the inclusion of learners with disabilities mediated by the use of digital technologies; challenges - deepening of the precariousness of teachers’ work, lack of continuous professional development opportunities, lack of inclusion public policies during pandemic.
Keywords: Covid-19 pandemic; Teaching experiences; Inclusive educational practices